Repeatability, Completion Time, and Predictive Ability of Four Diabetes-Related Foot Ulcer Classification Systems. (January 2023) - Alahakoon, Chanika; Fernando, Malindu; Galappaththy, Charith; Lazzarini, Peter; Moxon, Joseph V.; Jones, Rhondda; Golledge, Jonathan
Introduction: The inter and intra-observer reproducibility of measuring the Wound Ischemia foot Infection (WIfI) score is unknown. The aims of this study were to compare the reproducibility, completion times and ability to predict 30-day amputation of the WIfI, University of Texas Wound Classification System (UTWCS), Site, Ischemia, Neuropathy, Bacterial Infection and Depth (SINBAD) and Wagner classifications systems using photographs of diabetes-related foot ulcers. Methods: Three trained observers independently scored the diabetes-related foot ulcers of 45 participants on two separate occasions using photographs. The inter- and intra-observer reproducibility were calculated using Krippendorff's α. The completion times were compared with Kruskal-Wallis and Dunn's post-hoc tests. The ability of the scores to predict 30-day amputation rates were assessed using receiver operator characteristic curves and area under the curves. Results: There was excellent intra-observer agreement (α >0.900) and substantial agreement between observers (α=0.788) in WIfI scoring. There was moderate, substantial, or excellent agreement within the three observers (α>0.599 in all instances except one) and fair or moderate agreement between observers (α of UTWCS=0.306, α of SINBAD=0.516, α of Wagner=0.374) for the other three classification systems. The WIfI score took significantly longer ( P <.001) to complete compared to the other three scores (medians and inter quartile ranges of the WIfI, UTWCS, SINBAD, and Wagner being 1.00 [0.88-1.00], 0.75 [0.50-0.75], 0.50 [0.50-0.50], and 0.25 [0.25-0.50] minutes). None of the classifications were predictive of 30-day amputation ( P >.05 in all instances). Conclusion: The WIfI score can be completed with substantial agreement between trained observers but was not predictive of 30-day amputation.